Urine organic acid as the first clue towards aromatic L-amino acid decarboxylase (AADC) deficiency in a high prevalence area - Ling, Tsz-Ki; Wong, Ka-Chung; Chan, Candace Yim; Lau, Nike Kwai-Cheung; Law, Chun-yiu; Lee, Han-Chih Hencher; Lai, Chi-Kong; Chong, Yeow-Kuan; Yau, Kin-Cheong Eric; Cheung, Ka-Ming; Ko, Chun-Hung; Fung, Cheuk-wing; et al. (Clinica chimica acta, 2021)
Aromatic L-amino acid decarboxylase deficiency is a rare neurometabolic disease due to impaired decarboxylation of neurotransmitter precursors to its active form. Case: We retrospectively reviewed 8 cases from 2008 to 2019 with cerebrospinal fluid neurotransmitter analysis performed at our centre. All cases had an elevated urine vanillactic acid and, in most cases, with N-acetylvanilalanine detected. Cerebrospinal fluid analysis showed low downstream metabolites vanillylmandelic acid, homovanillic acid but high 3-O-methyl-L-DOPA, 5-hydroxytryptophan. Cerebrospinal fluid pterins were normal. Genotyping in DDC confirms the diagnosis. Urine organic acid analysis provided the first clue to diagnosis in four of the cases, which then triggered cerebrospinal fluid neurotransmitter and genetic analysis. We also developed a diagnostic decision support system to assist the interpretation of the mass spectrometry data from urine organic acids. Urine organic acid could be essential in guiding subsequent investigations for the diagnosis of aromatic L-amino acid decarboxylase deficiency. We propose to screen suspected cases first with urine organic acids, specifically looking for vanillactic acid and N-acetylvanilalanine. Suggestive findings should be followed with target analysis for c.714 + 4A > T in ethnically Chinese patients. The assistive tool allowed expedite interpretation of profile data generated from urine organic acids analysis. It may also reduce interpreter’s bias when peaks of interest are minor peaks in the spectrum.